Strategic Decision-Making to Increase Transaction Volume and Customer Loyalty at AHASS Bersama Jaya Prima - Zahran Hanawa; Pri Hermawan (International Journal of Science and Environment (IJSE), 2026)
The goal of this study was to find out how to make smart choices that would lead to more sales and more loyal customers at AHASS Bersama Jaya Prima, the official Honda workshop in Bekasi. Even though the economy is getting better again after the pandemic, their business is still stuck. This is mostly because service visits have dropped by about 40% from what they were before the pandemic. For this study, we ran a qualitative case study. We basically talked to key people, like the customers, the staff, and the suppliers, to understand the whole picture. The main way we analyzed the data was using Root Cause Analysis (5 Whys), and then we used the Theory of Planned Behavior (TPB) idea to explain what was going on. The results showed that the biggest problem is that things aren't run efficiently. Especially, they keep messing up the Standard Operating Procedures (SOPs) because everyone is so focused on serving many people fast instead of giving good quality service. This situation just gives customers a bad time, makes them wait longer, and makes them unhappy with the service. We then used Analytic Hierarchy Process (AHP) to pick the best move, and the clear winner was setting up a digital queue and booking system. This new system should help customers feel more in control (perceived behavioral control), fundamentally smooth out service bottlenecks, and definitely help bring customer loyalty back up so the business can recover properly.